Drawing and Knowledge Construction in Archaeology: The Aide Mémoire Project. (17th November 2021) - Morgan, Colleen; Petrie, Helen; Wright, Holly; Taylor, James Stuart
ABSTRACT: The Aide Mémoire Project conducted a survey and a series of observational studies in field recording and artifact illustration to understand 1) the perception of digital and by-hand drawing in archaeology, 2) how drawing contributes to the creation of mental models that allow archaeologists to understand archaeological remains and artifacts, and 3) what impact digital drawing has on the creation of these mental models. Our toolkit includes the NASA Task Load Index to assess and compare the mental load while drawing digitally or by-hand. We conclude that there are significant pedagogical, academic, and professional implications to consider when removing or replacing by-hand drawing with digital recording in archaeological methodology.